Access control models most used in medical data security - Campos-Montero, Brian (2024)
Unauthorized access to sensitive patient data is a problem that threatens themselves and the security of organizations dedicated to the health service, for which it is essential to implement access controls (CA), which must prevent access and use malicious data, for this reason an investigation was carried out based on a systematic review, using Prisma as a methodology; In addition, SCOPUS was used as a database including 82 articles, which served to find the most used access control models; therefore, 5 models were identified that were the most used (ABE, ABAC, RBAC, BBAC and MAC), representing a total of 52% of all the studies reviewed, while 29% belonged to those that were implemented only once and the remaining 19% to those that arose from solving problems identified within the 5 frequently used models.